Secretory Leukocyte Protease Inhibitor in Oral Potentially Malignant Disorders and Oral Squamous Cell Carcinoma - Ajila, Vidya; Babu, Subhas; Shetty, Veena; Hegde, Shruthi; Shenoy, Shilpa (Indian Journal of Medical and Paediatric Oncology, 2019)
Objectives: Secretory leukocyte protease inhibitor (SLPI) is a protein found in body fluids and implicated as a prognostic factor in many cancers. There is limited research regarding serum and salivary SLPI in oral potentially malignant disorders (OPMDs) and oral squamous cell carcinoma (OSCC). Materials and Methods: A total of 90 participants were included in the study; of which 30 formed the control group, 30 included participants with OPMD, and 30 included participants with OSCC. Serum and salivary levels of SLPI were estimated using enzyme-linked immunosorbent assay. Results: Serum levels of SLPI showed progressive increase in potentially malignant disorders and SCC patients when compared with controls, while salivary levels were increased in both OPMD and OSCC groups as compared to controls. However, the difference between groups was not statistically significant (P < 0.05). Conclusion: The above results suggest that increase in SLPI levels in the serum may have a role in indicating progression of OPMD to OSCC.
Keywords: Oral potentially malignant disorders; oral squamous cell carcinoma; saliva; Secretory leukocyte protease inhibitor; serum